National Crime Surveys: Victim Risk Supplement, 1983 ([Verlag nicht ermittelbar], 1985)
This special one-time survey was designed to collect data on persons aged 12 and over reporting household victimizations. The supplement, administered over a one-month period as part of the National Crime Survey, gathered data on people's lifestyles in order to determine whether certain lifestyles were related to crime victimization. Five questionnaires used by the Census Bureau for data collection served as the data collection model for this supplement. The first and second questionnaires, VRS-1 and VRS-2, contained basic screen questions and an incident report, respectively. VRS-3, the third questionnaire, was completed for every household member aged 16 or older, and included items specifically designed to determine whether a person's lifestyle at work, home, or during leisure time affected the risk of crime victimization. The interviewers completed the fourth and fifth questionnaires, VRS-4 and VRS-5. They were instructed to answer questions about the respondents' neighborhoods and behavior during the interview.